2009
DOI: 10.1007/s11845-009-0374-9
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery dissection following a minor household accident in a 10-month-old child

Abstract: A carotid artery dissection after minor trauma to the soft palate is a rare, but potentially severe complication. The combination of minor precipitating trauma, prolonged symptom-free intervals and complexity of clinical neurological assessment in small children contributes to a difficult diagnostic dilemma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Specifically, sudden acceleration/deceleration and rotation of the neck can stretch and compress the ICA causing dissection [6]. Different trauma types related to ischemic stroke cases are reported in Table 2 [4,6,7,[16][17][18][19][20][21][22][23][24][25][26][27], and it must be remembered that the trauma may be mild or even unnoticed [4,5]. Sports, fights, and falls can cause CAD, but motor vehicle accidents play the most important role [8].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, sudden acceleration/deceleration and rotation of the neck can stretch and compress the ICA causing dissection [6]. Different trauma types related to ischemic stroke cases are reported in Table 2 [4,6,7,[16][17][18][19][20][21][22][23][24][25][26][27], and it must be remembered that the trauma may be mild or even unnoticed [4,5]. Sports, fights, and falls can cause CAD, but motor vehicle accidents play the most important role [8].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed 21 published cases of ICAD caused by trauma. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These cases are summarized in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…In children from 1 mo up to 18 yr of age, 7.5% of arterial ischemic stroke is caused by carotid artery dissection [8]. Risk factors for carotid artery dissection are blunt neck trauma, tonsillectomy, adenotomy, other blunt oral trauma, and patients with collagen-vascular impairments (such as Marfan syndrome) [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%